2018
DOI: 10.1007/s00426-018-1070-z
|View full text |Cite
|
Sign up to set email alerts
|

When flow is not enough: evidence from a lane changing task

Abstract: Humans are able to estimate their heading on the basis of optic flow information and it has been argued that we use flow in this way to guide navigation. Consistent with this idea, several studies have reported good navigation performance in flow fields. However, one criticism of these studies is that they have generally focused on the task of walking or steering towards a target, offering an additional, salient directional cue. Hence, it remains a matter of debate as to whether humans are truly able to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…24 Indeed, the dose of HIIT we used in Fit 2 Drive has been linked to improvements in attention and reaction time, 14 which are vital cognitive functions that optimize vehicle tracking, lane keeping, driving performance, and therefore road safety. 25 The study findings also demonstrate feasibility aspects of Fit 2 Drive. The RPE data indicated that drivers were able to achieve vigorous intensity targets during HIIT depot sessions through a combination of stationary bike and circuit-based exercise modalities.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…24 Indeed, the dose of HIIT we used in Fit 2 Drive has been linked to improvements in attention and reaction time, 14 which are vital cognitive functions that optimize vehicle tracking, lane keeping, driving performance, and therefore road safety. 25 The study findings also demonstrate feasibility aspects of Fit 2 Drive. The RPE data indicated that drivers were able to achieve vigorous intensity targets during HIIT depot sessions through a combination of stationary bike and circuit-based exercise modalities.…”
Section: Discussionsupporting
confidence: 51%
“…Good levels of CRF also facilitate driver resilience to the endemic industry problems of sleep deprivation and fatigue, which in turn decrease the likelihood of road traffic accidents 24 . Indeed, the dose of HIIT we used in Fit 2 Drive has been linked to improvements in attention and reaction time, 14 which are vital cognitive functions that optimize vehicle tracking, lane keeping, driving performance, and therefore road safety 25 …”
Section: Discussionmentioning
confidence: 99%
“…Based on the texture, optic flow was available to participants even from the near ground. However, it has been suggested that optic flow alone is not sufficient to maintain a stable allocentric reference frame (Xu & Wallis, 2018 ). Concerning this possible reason, the question arises how the visual information about the allocentric reference frames could be strong enough for people to learn and use the CB strategy in the current task.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that visual feedback is needed in street following and that internal monitoring, if at all present, is not sufficient. The effect persists even if clear egomotion cues are provided without showing the streets margins, for example, by adding the optic flow of a cloud of random dots (Xu and Wallis 2020).…”
Section: Beyond Insectsmentioning
confidence: 99%